Predictors of high‐risk angiographic findings in patients with non‐ST‐segment elevation acute coronary syndrome. Issue 5 (13th November 2013) - Beigel, Roy; Matetzky, Shlomi; Gavrielov‐Yusim, Natalie; Fefer, Paul; Gottlieb, Shmuel; Zahger, Doron; Atar, Shaul; Finkelstein, Ariel; Roguin, Ariel; Goldenberg, Ilan; Kornowski, Ran; Segev, Amit; et al.
<x xml:space="preserve">Abstract</x> Background Current risk assessment of patients with non‐ST‐elevation acute coronary syndrome (NSTE‐ACS) may fail to identify some patients with severe coronary artery disease (CAD). We aimed to identify predictors of the angiographic extent and severity of CAD in patients with NSTE‐ACS undergoing early angiography and to evaluate its impact on prognosis. Methods We evaluated 923 patients with NSTE‐ACS who underwent coronary angiography. High‐risk coronary anatomy (HRCA) was defined as left main disease > 50%, proximal LAD lesion > 70%, or 2‐ to 3‐vessel disease involving the LAD. Clinical characteristics, in‐hospital, and 30‐day outcome and 1‐year mortality were compared between the high‐risk (N = 370) and the low‐risk groups (N = 553). Results Proportion of patients with elevated cardiac biomarkers was similar in both groups. The presence of peripheral vascular disease (OR = 1.88, 95% confidence interval [CI] = 1.62–5.80, P < 0.001) and a GRACE score of >140 (OR = 1.88, 95% CI = 1.29–2.75, P < 0.001) were the strongest predictors of HRCA. Patients with HRCA were prone to more complications during hospitalization and at 30 days (11.9% vs. 6%, P < 0.01) and increased 1‐year mortality (6.7% vs. 0.9%, P < 0.001). HRCA was the strongest predictor for 30‐day MACCE (OR = 2.32, 95% CI = 1.42–3.79, P < 0.001). HRCA (OR = 8.36, 95% CI = 1.01–69.4, P = 0.049; OR = 3.64, 95% CI = 1.2–11.07, P = 0.02) and GRACE score of >140 (OR = 6.86, 95% CI = 1.68–27.9, P = 0.007; OR = 4.84, 95% CI = 1.74–13.5, P = 0.002) were significant predictors of 30‐day and 1‐year mortality, respectively. Conclusions HRCA is predicted by clinical parameters and was not associated with elevated cardiac biomarkers. These patients fared worse when compared with those with low‐risk anatomy. We suggest that HRCA predictors should be included in the risk stratification of patients with NSTE‐ACS. © 2013 Wiley Periodicals, Inc.